Peran United Nations Commission on International Trade Law (UNCITRAL) dalam Harmonisasi Hukum Transaksi Perdagangan Elektronik (E-Commerce) Internasional - Dewi Lestari, Ni Putu; Ari Yuliartini Griadhi, Ni Made (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014)
This paper is entitled The Role of the United Nations Commission onInternational Trade Law (UNCITRAL) in the Harmonization of the Law of InternationalElectronic Commerce (E-Commerce) Transaction, also becomes the subject to study,especially about harmonizing the laws of each state on the international electroniccommerce (e-commerce) transactions. It applies normative legal research methodcombined with other relevant literature approach and statute approach. The conclusiondraw through this writing shall be means the UNCITRAL has a role to harmonize thetransaction of electronic commerce (e-commerce) by making a Model Law, that isUNCITRAL Model Law on Electronic Commerce 1996.
Keywords: Role, UNCITRAL, Harmonization, E-Commerce